2019
DOI: 10.1111/ctr.13697
|View full text |Cite
|
Sign up to set email alerts
|

Association of donor hypertension and recipient renal function in living donor kidney transplantation: A single‐center retrospective study

Abstract: Transplant centers now accept living donors with well‐controlled hypertension. Little is known whether hypertension in living donors affects recipient's kidney function. We aimed to examine potential differences in kidneys from hypertensive donors compared to normotensive donors with respect to renal function over 36 months and histologic findings at transplantation (T0) and 12 months after transplantation (T1). Retrospective single‐center analysis of 174 living donor‐recipient pairs (age > 18; transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(33 reference statements)
0
5
0
1
Order By: Relevance
“…These narrow donor criteria lead to the limited data on the outcomes of recipient of hypertensive living donors. In addition, there has been conflicting information about the impacts of donor hypertension on graft outcomes across several retrospective studies with small sample sizes [10,14,15,20,21]. A recent meta-analysis showed that donor hypertension was a weak, but significant risk factor for renal allograft failure (risk ratio of 1.31) [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These narrow donor criteria lead to the limited data on the outcomes of recipient of hypertensive living donors. In addition, there has been conflicting information about the impacts of donor hypertension on graft outcomes across several retrospective studies with small sample sizes [10,14,15,20,21]. A recent meta-analysis showed that donor hypertension was a weak, but significant risk factor for renal allograft failure (risk ratio of 1.31) [22].…”
Section: Discussionmentioning
confidence: 99%
“…All authors are grateful to KOTRY participating hospitals and investigators. We thank: Curie Ahn 1 , Jaeseok Yang 2 , Jin Min Kong 3 , Oh Jung Kwon 4 , Deok Gie Kim 5 , Cheol-Woong Jung 6 , Yeong Hoon Kim 7 , Joong Kyung Kim 8 , Chan-Duck Kim 9 , Ji Won Min 10 , Sung Kwang Park 11 , Yeon Ho Park 12 , Park Jae Berm 13 , Jung Hwan Park 14 , Jong-Won Park 15 , Tae Hyun Ban 16 , Sang Heon Song 17 , Seung Hwan Song 18 , Ho Sik Shin 19 , Chul Woo Yang 20 , Hye Eun Yoon 21 , Kang Wook Lee 22 , Dong Ryeol Lee 23 , Dong Won Lee 24 , Sam Yeol Lee 25 , Sang-Ho Lee 26 , Su Hyung Lee 27 , Jung Jun Lee 28 41 . in data acquisition, data analysis/interpretation, and statistical analysis.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Our findings among recipients of allografts from older donors with hypertension (mean donor age, 58 years) are consistent with prior, smaller studies. A German single‐center study ( N = 174) reported comparable allograft function three years post‐transplant in recipients whose donors had hypertension (mean donor age, 59 years) versus recipients whose donors did not have hypertension [15]. Similarly, a Japanese single‐center study ( N = 52) reported comparable allograft survival two years post‐transplant in recipients whose donors had hypertension (mean donor age, 67 years) versus recipients whose donors did not have hypertension [16].…”
Section: Discussionmentioning
confidence: 99%
“…Our study extends these inferences about allografts from older donors with hypertension with data from a large national cohort, followed up for thirteen years. Unlike prior studies where only outcomes in recipients of allografts from older donors with hypertension were investigated, [15–17] here, we additionally studied outcomes in recipients of allografts from younger donors. Our study reveals a higher risk of adverse outcomes among recipients of allografts from younger donors with hypertension (mean donor age, 42 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation